2016
DOI: 10.1002/cdq.12070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Goal Orientation Model of Vocational Identity

Abstract: The authors tested a model that considered goal orientation (mastery approach, performance approach, and performance avoidance) as an antecedent to vocational identity (career exploration and commitment) and included both career behaviors (career-related strategies) and affect (career distress) as outcomes of vocational identity. The authors also assessed vocational identity as a mediator for consistency with models of career development. The study was survey based with 281 young adult participants (77% women,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…First, supporting Hypothesis 1, we confirmed that vocational identity was related negatively to career goal–performance discrepancy (i.e., young adults with a stronger sense of vocational identity reported perceiving fewer career-related discrepancies). This finding is consistent with previous research, which has shown that young adults with a less well-defined vocational identity perceive more career-related obstacles and barriers (Gushue et al, 2006), report receiving more negative career-related feedback (Dobrow & Tosti-Kharas, 2012), and report higher levels of distress (Creed & Hennessey, 2016); whereas young people with more well-developed vocational identities are better able to deal with internal and external barriers, remain more connected to their vocational future (Diemer & Blustein, 2007), and seek less help with career and personal matters (Holland, Daiger et al, 1980). Our study provides evidence for a theoretical connection between vocational identity and career-related goal–performance discrepancies, which is consistent with the goal setting and self-regulatory approach (cf.…”
Section: Discussionsupporting
confidence: 92%
“…First, supporting Hypothesis 1, we confirmed that vocational identity was related negatively to career goal–performance discrepancy (i.e., young adults with a stronger sense of vocational identity reported perceiving fewer career-related discrepancies). This finding is consistent with previous research, which has shown that young adults with a less well-defined vocational identity perceive more career-related obstacles and barriers (Gushue et al, 2006), report receiving more negative career-related feedback (Dobrow & Tosti-Kharas, 2012), and report higher levels of distress (Creed & Hennessey, 2016); whereas young people with more well-developed vocational identities are better able to deal with internal and external barriers, remain more connected to their vocational future (Diemer & Blustein, 2007), and seek less help with career and personal matters (Holland, Daiger et al, 1980). Our study provides evidence for a theoretical connection between vocational identity and career-related goal–performance discrepancies, which is consistent with the goal setting and self-regulatory approach (cf.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this, career construction theory (Savickas, 2002) proposed that the construction of a vocational identity relies on career exploration, planning, decision-making, and career confidence. This reflects the general consensus in the career literature that vocational identity develops through engagement in various career development tasks and is shaped by a range of personal and contextual factors (Creed & Hennessey, 2016;Flum & Kaplan, 2006;Robitschek & Cook, 1999;Skorikov & Vondracek, 2011). Thus, the first objective of the present study was to assess the relationship between vocational identity and four career development tasks indicated by career construction (Savickas, 2002) and development (Flum & Kaplan, 2006;Super, 1990) theories (operationalized as career exploration, career planning, world-of-work information, and career certainty), using samples of Australian high school adolescents and their parents.…”
supporting
confidence: 60%
“…Stereotypes also hinder organizational or congregational cooperation, lead to irreconcilable leadership challenges, and cause confusion for leaders and followers alike or loss of credibility for women leaders (Dzubinski, 2016; Perry, 2013). Examples of gender role stereotypes can include men being viewed as having agency or confidence while women were viewed as having communal or nice behaviors (Creed & Hennessy, 2016; Dzubinski, 2016; Eagly & Johannesen-Schmidt, 2001; Eagly & Karau, 2002; Powell, Butterfield, & Bartol, 2008). Accepted leadership styles are beginning to expand to include agentic behaviors from female leaders (Embry, Padgett & Caldwell, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%